2022
DOI: 10.1002/cphc.202200078
|View full text |Cite
|
Sign up to set email alerts
|

Adding MgCl2 to Molten NaCl−UCln (n=3, 4): Insights from First‐Principles Molecular Dynamics

Abstract: Molten chlorides are proposed for fast‐spectrum molten salt reactors. Molten MgCl2 with NaCl forms eutectic mixtures and is considered as a promising dilutant to dissolve fuel salts such as UCl3 and UCl4. A previous study suggests the formation of a U−Cl network at the U : Na=1 : 1 binary salt. However, it is unclear how the structure of UCln (n=3, 4) in NaCl will change after adding MgCl2 in the salt. Here, we use first‐principles molecular dynamics to investigate the molten ternary salts NaCl−MgCl2−UCln (n=3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(50 reference statements)
0
3
0
Order By: Relevance
“…For high accuracy, MD methods that employ the use of quantum mechanics (QM) or first-principles MD (FPMD) are used to determine the energies and forces. Unfortunately, FPMD can be computationally expensive and is generally limited to molten salt simulations of relatively small (≤200 atoms) systems at short time scales (≤100 ps). This places a significant limitation on the use of FPMD, since properties such as melting point, thermal conductivity, ionic conductivity, diffusion coefficients, or viscosity typically require MD simulations of thousands of atoms at nanosecond time scales.…”
Section: Introductionmentioning
confidence: 99%
“…For high accuracy, MD methods that employ the use of quantum mechanics (QM) or first-principles MD (FPMD) are used to determine the energies and forces. Unfortunately, FPMD can be computationally expensive and is generally limited to molten salt simulations of relatively small (≤200 atoms) systems at short time scales (≤100 ps). This places a significant limitation on the use of FPMD, since properties such as melting point, thermal conductivity, ionic conductivity, diffusion coefficients, or viscosity typically require MD simulations of thousands of atoms at nanosecond time scales.…”
Section: Introductionmentioning
confidence: 99%
“…Molten salt mixtures of the actinides or lanthanides are becoming quite useful for industry and in the energy sector. For example, UCl 3 –NaCl–MgCl 2 and PuCl 3 –NaCl–MgCl 2 are promising molten salt fast reactor fuel candidates, , LaCl 3 –KCl–MgCl 2 mixtures are used to synthesize various LaMg alloys used as tunable mirrors, and various Cl – -based mixture melts have been studied in the context of corrosion. It is also important to have fast database access to thermodynamic properties of complex binary and ternary salt combinations. There is a direct link between structural and thermodynamic studies such as ours and the quasi-thermodynamic models that are at the core of such databases since free-energetic properties in those are modeled based on the coordination number of the ions. Of course, in reality it was found that, at the temperatures at which salts are in the molten state, cations have an ensemble of interconverting coordination structures that are temperature dependent. For multivalent cations in combination with chloride, a significantly polarizable anion, there are further complexities.…”
Section: Introductionmentioning
confidence: 99%
“…Molten salt mixtures of the actinides or lanthanides are becoming quite useful for industry and in the energy sector. For example, UCl 3 –NaCl–MgCl 2 and PuCl 3 –NaCl–MgCl 2 are promising molten salt fast reactor fuel candidates, 1 , 2 LaCl 3 –KCl–MgCl 2 mixtures are used to synthesize various LaMg alloys 3 used as tunable mirrors, 4 and various Cl – -based mixture melts have been studied in the context of corrosion. 5 9 It is also important to have fast database access to thermodynamic properties of complex binary and ternary salt combinations.…”
Section: Introductionmentioning
confidence: 99%